2019
DOI: 10.3390/nano9091272
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics Contributions to the Growth Mechanism of Ga2O3 Thin Film and NWs Enabled by Ag Catalyst

Abstract: In the last few years, interest in the use of gallium oxide (Ga2O3) as a semiconductor for high power/high temperature devices and UV nano-sensors has grown. Ga2O3 has an enormous band gap of 4.8 eV, which makes it well suited for applications in harsh environments. In this work, we explored the effect of Ag thin film as a catalyst to grow gallium oxide. The growth of gallium oxide thin film and nanowires can be achieved by heating and oxidizing pure gallium at high temperatures (~1000 °C) in the presence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…The growth morphologies of gallium oxide were studied on various substrates and at different oxidation temperatures. Previous work has shown that crystalline the Ga 2 O 3 phase was obtained under the same oxidation conditions used in this work [ 2 , 22 ]. Because the oxidation conditions were kept constant in this work, the nanostructures formed during oxidation are primarily related to the substrate.…”
Section: Resultsmentioning
confidence: 71%
See 3 more Smart Citations
“…The growth morphologies of gallium oxide were studied on various substrates and at different oxidation temperatures. Previous work has shown that crystalline the Ga 2 O 3 phase was obtained under the same oxidation conditions used in this work [ 2 , 22 ]. Because the oxidation conditions were kept constant in this work, the nanostructures formed during oxidation are primarily related to the substrate.…”
Section: Resultsmentioning
confidence: 71%
“…During the oxidation of the substrates in the presence of Ag, additional temperature-dependent processes influenced both the nucleation and the growth of nanostructures. Ga 2 O 3 nucleation in the presence of Ag was greatly influenced by the oxidation temperatures due to the high oxygen diffusivity and solubility in silver at higher temperatures [ 2 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sensors obtained using this innovative approach will lead to new trends in design, control, and applications of real-time intelligent sensor system control by advanced intelligent control methods and techniques. The effect of Ag thin film as a catalyst to enhance the growth of Ga 2 O 3 nanowire and crystalline thin film on quartz has been reported [29], but it has not been explored on the silicon surface. We also wanted to observe the contribution of silicon atoms in enhancing the conductivity of Ga 2 O 3 nanowires via diffusion-enabled incorporation into the nanowires during the growth process.…”
Section: Introductionmentioning
confidence: 99%